Pengenalan Gizi Seimbang serta Pola Hidup Bersih dan Sehat (PHBS) di SDN Jambewungu 01 Bondowoso - Agung Nugroho Puspito; Mohammad Ubaidillah; Hasbi Mubarak Suud; Aulia Rafidah Pananto; Clara Sintha Putri Pratiwi; Dodik Priyanto; Keysa Churiyyatul Haris; Nabila Safira Putri Madani; Naiya Nalya Cahyadi; Telpivani Solehatul Putri Untari (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This social project aims to open up elementary school students' views regarding nutrition and a Clean and Healthy Lifestyle (PHBS). Apart from that, it aims to change their behavior by implementing PHBS in their daily lives, such as washing their hands regularly, exercising regularly, and throwing rubbish in the right place. Community Service was carried out at SDN Jambewungu 1, Wringin District, Bondowoso Regency with a total of 88 students from grades 1 to 6. The method used is a conventional method which involves presentation, practice and discussion in implementation. The results of community service show that the knowledge and insight of students at SDN Jambewungu 1 increased by 40% regarding their understanding or mastery of nutrition, hygiene and personal health material which we adopted as the main material in service activities.